Mitochondrial dynamism and the pathogenesis of Amyotrophic Lateral Sclerosis - Cozzolino, Mauro; Rossi, Simona; Mirra, Alessia; Carrì, Maria Teresa (Frontiers in Cellular Neuroscience, 2015)
Research on mitochondria in the last years has been characterized by the fundamental finding that the morphology of mitochondria is deeply connected to the regulation of a vast number of different processes, including oxidative phosphorylation and ATP production, calcium buffering, and apoptosis. This has immediately focused the attention of the neuroscience community to the possible involvement of mitochondrial dynamism, the process underlying morphological features of mitochondria, in neurodegeneration, where mitochondrial dysfunction is believed to represent an important contributing event, or even a primary causative factor. Amyotrophic Lateral Sclerosis, a disease of motor neurons and their neighboring cells, has long been considered as a neurodegenerative disease with an important mitochondrial issue. Yet, whether mitochondria have a causative, primary role in the pathogenic process has always been debated, and the specific defects which account for this role are elusive. Here we discuss recent genetic advances suggesting that defective mitochondrial dynamism is primarily involved in the pathogenic mechanisms of ALS, and that foster the longstanding concept that disruption of mitochondrial function is a vulnerable factor for motor neurons.